COMMUNITY EMPOWERMENT DISCOURSE IN THE NATIONAL DEVELOPMENT POLICY - Aris Munandar (Journal of Social Political Sciences, 2021)
This paper is a literature study on issues, concepts, and strategies for empowerment in the discourse of development in Indonesia. The discourse of community empowerment in Indonesia's national development, in principle, is not something new. Philosophically and normatively, the ideals of community empowerment as the goal of national development have been strengthened in the 1945 Constitution as the constitutional foundation of the Unitary State of the Republic of Indonesia. However, at the practical level, these ideal goals are not implemented in the implementation of the national development program. Poverty and inequality are still crucial issues, even though the Reformation era, which represents a democratic government, has been running for two decades.